(untitled) (Sociologisk Forskning, 2007)
The Norrliden project. Genderisation and ethnification of a low status residential area in the local press Media often contributes to segregation by constructing low status residential areas as “different” from what is “normal” and “Swedish”. Research into media representations of these residential areas often focuses big city contexts. Furthermore, research tends to be preoccupied with the construction of ethnic differences, paying little attention to the relationship between construction processes of gender and ethnicity. This article is a critical analysis of how the local daily newspapers in a medium sized town, Kalmar, construct stereotypes of immigrants and gendered identities in the low status residential area Norrliden. Two newspapers were studied in search for articles related to the area, published during the year 2005. Despite the newspapers’ claim that they want to contribute to a more nuanced and less stereotyped image of the residential area the consequences of their work seem to be the opposite. The representation sof the area are coded with stereotypes suggesting that the area is unsafe and dangerous and that the people who live there are motivated by affect and emotions rather than by successful socialisation. These representations are also characterised by notions of ethnicity and gender, as well as class. Norrliden is described as an area in need of change and improvement, as an unfinished project dependent upon aid from the outside. A reading of the 2005 media representations of Norrliden exposes an example of “symbolic violence” in that texts and photographs repeatedly degrade the area and its inhabitants.